PUBLIC VALUE PENGGUNA LAYANAN TRANSPORTASI PUBLIK TRANSJAKARTA DI JAKARTA SELATAN - Zahreina Nurul Ramadhany; Endang Larasati Setianingsih (Journal of Management and Public Policy, 2026)
Public transportation plays a vital role in supporting the mobility of urban communities and reducing traffic congestion. TransJakarta, as a Bus Rapid Transit (BRT) service in Jakarta, is expected to create public value through effective, affordable, and reliable service. This study aims to analyze the public value perceived by TransJakarta users in South Jakarta and to identify the factors that support and hinder it. This study employs a descriptive qualitative approach using data collection techniques such as interviews, observations, and documentation. The analysis utilizes Mark H. Moore’s Strategic Triangle framework with indicators developed by Wijewardena (2009), encompassing legitimacy and support, operational capabilities, and public value. The results indicate that TransJakarta services generally reflect these three dimensions through government policy support, adequate operational capacity, and public value in the form of affordability, service integration, and service responsiveness. However, challenges remain regarding service communication by staff and the equitable distribution of bus stop facilities.